Effect of row arrangement of common bean with maize intercropping on yield and economic benefit of component crops under Gimbo and Guraferda, Kaffa and Bench Maji zones, South Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2020)
The yield advantage obtained due to intercropping is attributed to a better use of resources by crops grown in combinations, as compared to sole stands. Field experiment conducted at Gimbo and Guraferda during 2017 and 2018 cropping seasons in order to determine the appropriate intercropping row arrangement on maize-common bean yield and economic advantages of the cropping system. Maize variety BH-540 and common bean variety Hawassa dume were used as test crop. The experiment used four treatments (sole maize, sole common bean, 1:1 maizecommon bean and 1:2 maize-common bean intercropping) arranged in a randomized complete block design with four replications. Grain yield of the component crops were significantly varied by locations. The highest maize yield was recorded at Guraferda than Gimbo; whereas, common bean yielded better at Guraferda than at Gimbo. The combined mean grain yield of maize and common bean was significantly (p